PHONEMIC DISTRIBUTION AND FREQUENCY ANALYSIS (Web of Discoveries: Journal of Analysis and Inventions, 2025)
This study explores the distribution and frequency of phonemes in several languages, emphasizing their role in phonological structure and linguistic analysis. The research compares phoneme usage in English, Uzbek, Korean, and Russian through a combination of corpus-based methods and phonological theory. Key findings reveal that phonemic frequency is not randomly distributed but rather shaped by phonotactic rules, historical development, and articulatory economy. The results contribute to a deeper understanding of language-specific phonemic hierarchies and provide implications for language learning, phonological modeling, and speech recognition systems.